A new research challenge persuasive technology to motivate healthy aging. - Intille, S.S (IEEE Transactions on information technology in biomedicine)
Healthcare systems in developed countries are experiencing severe financial stress as age demographics shift upward, leading to a larger percentage of older adults needing care. One way to potentially reduce or slow spiraling medical costs is to use technology, not only to cure sickness, but also to promote wellness throughout all stages of life, thereby avoiding or deferring expensive medical treatments. Ubiquitous computing and context-aware algorithms offer a new healthcare opportunity and a new set of research challenges: exploiting emerging consumer electronic devices to motivate healthy behavior as people age by presenting "just-in-time" information at points of decision and behavior